An Early Recording of Welsh from the Berliner Lautarchiv; David Evans at Ruhleben Camp in 1917. (1st January 2017) - Awbery, G. M.
During the First World War an extensive programme of sound recording was carried out by the Königliche Preussische Phonographische Kommission. Civilian and military internees in POW camps in Germany were recorded, in order to collect samples of as many different languages and dialects as possible. Among them was one Welsh-speaker, David Evans from Blaenffos in Pembrokeshire. This paper explores the background to the recordings which he made in 1917, and examines in detail the actual material recorded.